Acute Kidney Injury After Pediatric Cardiac Surgery: A Secondary Analysis of the Safe Pediatric Euglycemia After Cardiac Surgery Trial*. Issue 7 (July 2017) - Blinder, Joshua J.; Asaro, Lisa A.; Wypij, David; Selewski, David T.; Agus, Michael S. D.; Gaies, Michael; Ferguson, Michael A.
Abstract : Objectives: To understand the effect of tight glycemic control on cardiac surgery–associated acute kidney injury. Design: Secondary analysis of data from the Safe Pediatric Euglycemia after Cardiac Surgery trial of tight glycemic control versus standard care. Setting: Pediatric cardiac ICUs at University of Michigan, C.S. Mott Children's Hospital, and Boston Children's Hospital. Patients: Children 0–36 months old undergoing congenital cardiac surgery. Interventions: None. Measurements and Main Results: Cardiac surgery–associated acute kidney injury was assigned using the Acute Kidney Injury Network criteria with the modification that a greater than 0.1 mg/dL increase in serum creatinine was required to assign cardiac surgery–associated acute kidney injury. We explored associations between cardiac surgery–associated acute kidney injury and tight glycemic control and clinical outcomes. Of 799 patients studied, cardiac surgery–associated acute kidney injury occurred in 289 patients (36%), most of whom had stage II or III disease (72%). Cardiac surgery–associated acute kidney injury rates were similar between treatment groups (36% vs 36%; p = 0.99). Multivariable modeling showed that patients with cardiac surgery–associated acute kidney injury were younger ( p = 0.002), underwent more complex surgery ( p = 0.005), and had longer cardiopulmonary bypass times ( p = 0.002). Cardiac surgery–associated acute kidney injury was associated with longer mechanical ventilation and ICU and hospital stays and increased mortality. Patients at University of Michigan had higher rates of cardiac surgery–associated acute kidney injury compared with Boston Children's Hospital patients (66% vs 15%; p < 0.001), but University of Michigan patients with cardiac surgery–associated acute kidney injury had shorter time to extubation and ICU and hospital stays compared with Boston Children's Hospital patients. Conclusions: Tight glycemic control did not reduce the cardiac surgery–associated acute kidney injury rate in this trial cohort. We observed significant differences in cardiac surgery–associated acute kidney injury rates between the two study sites, and there was a differential effect of cardiac surgery–associated acute kidney injury on clinical outcomes by site. These findings warrant further investigation to identify causal variation in perioperative practices that affect cardiac surgery–associated acute kidney injury epidemiology. Abstract : Supplemental Digital Content is available in the text.